The stratigraphy and tectonics of the area north-northeast of the city Van - Aksoy, E.; Tatar, Y. (My University, 1990)
In the studied area, which is located to the north-northeast of Van city, Mesozoic magmatic rocks and Cenozoic sedimentary rocks crop out. Allochthonous Upper Cretaceous Complex is represented by andesites, andesitic tuffs, dacites, dacitic tuffs, diabases, basalts-andesitic basalts and mudstones. The magmatics of the unit are of calc-alkaline character and they are interpreted to be the products of an island arc volcanism. The unit is affected by a low-grade metamorphism. Parallochthonous Kirkgecit Formation, which consist of conglomerate, sandstone and mudstone alteration, is of Middle Eocene-Early Miocene. Plio-Quaternary lake sediments, which are named as Van Formation in this study, are composed of poorly welded pebble, sand and clay layers. The fold axes trend and the thrust fault strikes roughly in E-W. These orientations indicate that the area was subjected to a N-S compressional stress which was the result of the relative movement of Arabian Plate towards the north during the Alpine Orogeny. -from English summary
Van ili dogu-kuzeydogu yoresinin stratigrafisi ve tektonigi
Keywords: Turkey; Van; economic geology; lake sediment; magmatism; metamorphism; stratigraphy; tectonics